Applications of implementation science (IS) in learning health systems (LHS): a scoping review protocol - Carol Mita; Aimee K Huang; Rachel Vanderkruik; Salma Argueta; Stephen J Bartels (BMJ Open)
Introduction Despite advancements in biomedical and healthcare research, the translation of evidence into routine practice within healthcare systems often lags, perpetuating inefficiencies and disparities in care delivery. Learning health systems (LHS), which integrate internal data and external evidence for continuous improvement, hold promise for addressing these gaps. Implementation science (IS), focused on promoting the systematic uptake of evidence-based practices, offers a robust framework to drive sustainable improvements within LHS. However, the practical application of IS principles in LHS remains underexplored. This scoping review aims to systematically map the literature on the application of IS in LHS, highlighting themes, gaps and opportunities for advancing future practices.Methods and analysis This review will follow the Joanna Briggs Institute (JBI) methodology for scoping reviews, supported by the Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews (PRISMA-ScR) checklist. The review employs a population-concept-context framework, focusing on studies engaged in LHS activities and the application of IS principles in various healthcare settings. Relevant literature will be searched across multiple databases, including OVID/Medline, Embase, Web of Science Core Collection and Health Policy Reference Center. Eligible studies will be screened, and data will be extracted and synthesised using both quantitative and qualitative methods. Key outcomes include characterising IS applications in LHS, evaluating barriers and facilitators, exploring equity integration, and identifying knowledge gaps.Ethics and dissemination As this study does not involve primary data collection, ethical approval is not required. Findings will be disseminated through peer-reviewed publications and conference presentations to inform future research and practice.Registration This protocol has been registered on the Open Science Framework (DOI: 10.17605/OSF.IO/BMQ6J).